1988
DOI: 10.1083/jcb.107.6.2483
|View full text |Cite
|
Sign up to set email alerts
|

Import pathways of precursor proteins into mitochondria: multiple receptor sites are followed by a common membrane insertion site.

Abstract: Abstract, The precursor of porin, a mitochondrial outer membrane protein, competes for the import of precursors destined for the three other mitochondrial compartments, including the Fe/S protein of the bctcomplex (intermembrane space), the ADP/ATP carrier (inner membrane), subunit 9 of the F0-ATPase (inner membrane), and subunit 13 of the F,-ATPase (matrix). Competition occurs at the level of a common site at which precursors are inserted into the outer membrane. Protease-sensitive binding sites, which act be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
116
1

Year Published

1990
1990
1994
1994

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(123 citation statements)
references
References 52 publications
6
116
1
Order By: Relevance
“…The GIP-complex can be co-immunoprecipitated with antibodies against MOM19 [10]. Evidence for the existence of a general insertion pore has been obtained from the observation that this site can be saturated by chemical amounts of porin precursors [16] and that the ADP/ATP carrier in the absence of a membrane potential can accumulate at the GIP-site in a proteinase-protected location [17].…”
Section: The Receptor Complex Of the Outer Membranementioning
confidence: 99%
“…The GIP-complex can be co-immunoprecipitated with antibodies against MOM19 [10]. Evidence for the existence of a general insertion pore has been obtained from the observation that this site can be saturated by chemical amounts of porin precursors [16] and that the ADP/ATP carrier in the absence of a membrane potential can accumulate at the GIP-site in a proteinase-protected location [17].…”
Section: The Receptor Complex Of the Outer Membranementioning
confidence: 99%
“…Precursor proteins then become inserted into a transport pore in the outer membrane (Pfanner et al, 1987a). Since competition studies revealed that many precursor proteins use the same pore for insertion into the outer membrane, this was termed general insertion pore GIP (Pfaller et al, 1988;Pfanner, Hartl & Neupert, 1988).…”
Section: Abstract: Mitochondrial Receptor Complex--general Insertionmentioning
confidence: 99%
“…Four of these proteins, MOM7, MOM8, Abbreviations: TMS, transmembrane spanning segments; Ab, antibodies; ND, not determined; N, amino-terminus; C, carboxy-terminus; GIP, general insertion pore; S.c., Saccharomyces cerevisiae MOM30 and MOM38, are believed to be involved in the formation of the general insertion pore GIP that is responsible for the insertion of preproteins into the outer membrane and their translocation across this membrane (Pfaller et al, 1988). The ability of the mitochondria to form the GIP-intermediate of the AAC was lost upon protease treatment in a manner similar to the degradation of MOM19, MOM22 and MOM72; in contrast, the ability to transfer the AAC precursor from the GIP-stage into the inner membrane was resistant to much higher protease concentrations and correlated with the integrity of MOM38 (Table).…”
Section: A Protein Complex In the Mitochondrial Outer Membrane Contaimentioning
confidence: 99%
“…A fraction of MOM19 and MOM72 molecules associate with a 38 kDa outer membrane protein (MOM38) to form a high molecular mass complex, termed the mitochondrial receptor complex (Pfaller, R., S~511ner, T., Griffiths, G., Pfanner, N. and Neupert, W., unpublished data). MOM38 appears to be related to the general insertion protein (GIP) that is responsible for the insertion of precursors into the outer membrane [8]. The mitochondrial receptor complex might be preferentially located in contact site regions.…”
Section: Components Of Mitochondrial Contact Sitesmentioning
confidence: 99%
“…The precursors are recognized by specific receptor proteins on the mitochondrial surface; two receptors were identified recently and termed MOM19 and MOM72 (for mitochondrial outer membrane proteins of 19 and 72 kDa, respectively) [6,7]. The precursors are inserted into the outer mitochondrial membrane [8], and are translocated into and across the inner membrane mainly at sites of close contact between both membranes [9]. The entrance of precursors into the inner membrane depends on the membrane potential A,/, across the membrane [10].…”
Section: Introductionmentioning
confidence: 99%